ANALISIS TINGKAT ADOPSI INOVASI BUDIDAYA IKAN LELE SANGKURIANG (Clarias gariepinus) DENGAN SISTEM TEKNOLOGI BIOFLOK PADA ANGGOTA KELOMPOK CLARIAS SP DI KELURAHAN TERITIP KOTA BALIKPAPAN - Abi Aufaturrahman; Nurul Ovia Oktawati; Sumoharjo (2339-1324, 2018)
The purposive of this research was to analyze the characteristics correlation of internal, external, and innovation to the level of sangkuriang catfish (Clarias gariepinus) farming innovation adoption with biofloc technology system and to determine the level of adoption of Clarias sp group in receiving bioflok technology system. This research was conducted from Desember 30, 2016 to Januari 12, 2017 in Teritip Village, Balikpapan City. The sampling method used was sensus method with the number of respondents as many as 13 persons. The rank spearman correlation was to analysis the correlation of all characteristics. The analysis showed that the internal characteristics; age was closely related to the interest and cosmopolitan very closely related to the interest and trial. The external characteristics; the role of group leader closely related to the aware and the role of the mass media was closely related to the interest. Characteristics of innovation; compatibility was very closely related to evaluate and closely related to trial while triability closely related to evaluate and very closely related to the trial. Clarias sp group was able to receive the most optimal biofloc technology to the level of interest.